Prevention of symptomatic neuroma in traumatic digital amputation: A RAND/UCLA appropriateness method consensus study. (December 2020) - Crosio, Alessandro; Albo, Erika; Marcoccio, Ignazio; Adani, Roberto; Bertolini, Maddalena; Colonna, Michele Rosario; Felici, Nicola; Guzzini, Matteo; Atzei, Andrea; Riccio, Michele; Titolo, Paolo; Tos, Pierluigi
Highlights: The formation of a neuroma after finger amputation is frequent and prevention techniques are not validate. Using the RAND/UCLA appropriateness protocol a selection of procedures described in literature have been analysed by Italian Hand Surgeons. The panelists suggested that, even if all the described procedures were applied, unpredictable results in neuroma prevention are presumable. Appropriate procedures are: treatment in operating room, identify neurovascular bundles, treatment of local soft tissues. Abstract: Introduction: The appearance of a symptomatic neuroma following finger amputation is a devastating consequence for patient's quality of life. It could be cause of chronic neuropathic pain. The prevention of neuroma formation is a challenging effort for hand surgeons. The biological mechanisms leading to neuroma formation are mostly unknown and different preventing procedures have been tried without certain results. In this paper, a panel of Italian hand surgeons have been asked to express appropriateness about potentially preventive techniques of neuroma formation following the RAND/UCLA appropriateness protocol. Methods: A literature review was preliminarily performed identifying the most employed methods to reduce the pathologic nerve scar. Afterwards, the selected panelists were asked to score the appropriateness of each procedure in a double scenario: in case of a sharp amputation or in a tear injury. The appropriateness was evaluated according to RAND/UCLA protocol. Results: Nine Italian hand surgeons were included in the panel. Of them 5 were orthopaedic surgeons, 4 plastic surgeons. The identified appropriate procedures were: revision amputation should be done in operating room, the neurovascular bundles should be identified and is mandatory to treat surrounding soft tissues. Only in case of clean-cut amputation, it is appropriate to perform a proximal extension of the dissection, to use diathermocoagulation and coverage with local flaps. Procedures such as shortening in tension of the nerve stump, bone shortening, implantation of the nerve end in the soft tissue, treatment in the emergency room and, in both scenarios, certain results are evaluated as uncertain. Discussion: In order to prevent the formation of a distal stump neuroma few methods were judged appropriate. It is mandatory to identify the neurovascular bundles and treat also the surrounding tissues, but no certain results could be obtained with local flap, bone shortening and other ancillary surgical acts. Moreover, it is not possible to guarantee the non arising of neuroma in any cases, also when every procedure has been temped. Conlusions: The prevention of distal neuroma is actually a challenge, without a well known strategy due to the variability of response of nervous tissue to injury.